2022
DOI: 10.3389/fcell.2022.913824
|View full text |Cite
|
Sign up to set email alerts
|

Huaier Induces Immunogenic Cell Death Via CircCLASP1/PKR/eIF2α Signaling Pathway in Triple Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is the most lethal breast cancer subtype owing to the lack of targeted therapeutic strategies. Immunogenic cell death (ICD), a modality of regulated cancer cell death, offered a novel option for TNBC via augmenting tumor immunogenic microenvironment. However, few ICD-inducing agents are currently available. Here, we showed that Trametes robiniophila Murr (Huaier) triggered ICD in TNBC cells by promoting cell surface calreticulin (CRT) exposure, and increasing release of ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The overexpression of circCLASP1, the third upregulated circRNA in the present study, greatly enhanced the stimulating effects of Huaier-induced immunogenic cell death. 23 A recent study showed that Wnt7a was also a fibrotic target gene. 24 Interestingly, circCLASP1 was upregulated in bd/db mice with cardiac fibrosis, and may regulate Wnt7a by inhibiting the activity of miR-182-5p.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of circCLASP1, the third upregulated circRNA in the present study, greatly enhanced the stimulating effects of Huaier-induced immunogenic cell death. 23 A recent study showed that Wnt7a was also a fibrotic target gene. 24 Interestingly, circCLASP1 was upregulated in bd/db mice with cardiac fibrosis, and may regulate Wnt7a by inhibiting the activity of miR-182-5p.…”
Section: Discussionmentioning
confidence: 99%
“…4T1 cells were treated with free JQ1, free CXB, JQ1/CXB physical mixture, or CS@JQ1/CXB for 24 h, separately. Then, the cells were harvested and lysed with SDS lysis buffer, and the protein concentrations were measured by the BCA protein assay kit. , The cell lysates containing 30 μg protein were separated by SDS-PAGE at 100 V for 1 h and then transferred onto the PVDF membranes under the ice bath conditions at a transfer current of 0.25 A. Afterward, the membranes were incubated with primary antibodies against GAPDH (1:1000), PD-L1 (1:500), COX-2 (1:500), and VEGF (1:500), and secondary horseradish peroxidase-linked antibodies.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…This anti‐tumor effect was mainly associated with ER stress‐associated ICD by promoting the exposure to CRT, release of ATP and HMGB1 in TNBC cells. Further study found that the induction of ICD was triggered through circCLASP1/PKR/eIF2α signaling pathway 108 . MHO7 (6‐epi‐ophiobolin G), a small molecule from Aspergillus ustus , elicited cytotoxic effect on TNBC cells at a low IC 50 from 0.96 to 1.75 μM.…”
Section: Crosstalk Between Microbes and Icd In Cancer Developmentmentioning
confidence: 99%